-36a^2-96ab-64ab^2 how to factor this problem


36=6^2,64=8^2 and 96=6*8*2
hence we see using the formula (a+b)^2=a^2+2ab+b^2 that -36a^2-96ab-64b^2=-(6a+8b)^2

Edit : oops I didn't see the last part was 64ab^2 and not 64b^2, disregard the answer

Rate answer


-36a² - 96ab - 64ab²
-36a² - 48ab - 48ab - 64ab
(-6a - 8b)(6a + 8b)


Rate answer
Wrong answer?

If your question is not fully disclosed, then try using the search on the site and find other answers on the subject Mathematics.

Find another answers

Load image